The Drawbacks and Advantages of Tiktok in Student Amid Pandemic Covid-19 - Bahagia, Bahagia; Wibowo, Rimun; Muniroh, Leny; Wahid, Azhar Al; Rizkal, Rizkal; Noor, Zakky Muhammad; Karim, Abdul (Universitas Pahlawan Tuanku Tambusai, 2022)
Tiktok has become a part of life in today's digital era. This study aims to find out the negative and positive effects of TikTok on school children. This study uses a qualitative method. The sampling technique was carried out purposively, namely school teachers. Data were collected through in-depth interviews. The sample was selected through a purposive technique. The results were carefully examined through triangulation and source triangulation techniques. The results show that Tiktok is a digital literacy method for students so they can keep up with the times. Tiktok is also a fairly good learning medium for students when the content of TikTok includes religious lectures, religious values, and moral values that exist in religion. Even TikTok is useful as an interesting learning medium for students during a pandemic when teachers use TikTok as material for distributing material. The features of TikTok make the material interesting for children because of the many color combinations, music, and not boring. Plus there are economic values because TikTok is also a trading medium for many people. This is a trigger for entrepreneurship education for students. However, TikTok also has a bad impact on children because school children can spend time playing TikTok, spending cellphone credit, being lazy, and following the TikTok style that is not following religious teachings. The attitude of children who are still imitating can imitate what is seen on TikTok. For this reason, parents play a role in supervising children by looking at the history of what children open on their cellphones and giving understanding to which children are worthy to be seen and which are not